HIV and Liver Disease - Sherman, Kenneth E.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Liver disease has been identified as a leading cause of death in HIV-infected patients since the introduction of highly active antiretroviral therapy (HAART) in 1996. The HIV treatment community has been caught largely unaware of this emerging dilemma. Many HIV care providers are ill-equipped to understand and interpret liver injury patterns, or to provide comprehensive care and management for viral coinfections which they are not familiar with. HIV and Liver Disease provides a comprehensive update of the field covering the epidemiology, pathogenesis, management and treatment of liver disease in patients with HIV infection. The volume will help HIV care providers understand and interpret liver injury patterns, and/or provide comprehensive care and management for viral coinfections. Gastroenterologists and hepatologists will gain an understanding of complex drug regimens that are used to treat HIV and which may impact HCV and HBV treatment. Written by expert clinicians and researchers across multiple disciplines, HIV and Liver Disease will be of great value to gastroenterologists, hepatologists, infectious disease practitioners, as well as other health care providers who provide care or participate in research in the field of HIV.
Preface -- The HIV Epidemic in the United States - Current Trends, 2010 -- Epidemiology of Liver Disease in Human Immunodeficiency Virus Infected Persons -- Current and Future  Treatment Guidelines for HIV -- Pathology of HIV-Associated Liver Disease -- Non-invasive Markers of Liver Injury and Fibrosis -- Mechanisms of Alcoholic Steatosis/Steatohepatitis -- Immunopathogenesis of Liver Injury -- Host Gene Polymorphisms and Disease/Treatment Outcomes in HIV and Viral Co-infections -- Effects of HIV on Liver Cell Populations -- HIV Replication -- Hepatitis C - Natural History -- Natural History of Hepatitis B Virus in HIV-Infected Patients -- Other Hepatitis Viruses and HIV Infection -- Hepatitis B Virus:  Replication, Mutation and Evolution -- Hepatitis C Virus Treatment in HIV -- Treatment of Hepatitis B in HIV-Infected Persons -- Prevention of Hepatitis Infection in HIV-Infected Patients -- Alanine Aminotransferase (ART) Hepatotoxicity -- Management of End Stage Liver Disease and the Role of Liver Transplantation in HIV infected Patients -- Assessment and Treatment of Alcohol and Substance Use Disorders in Patients with HIV Infection -- Racial Disparities in HIV and Liver Disease -- Quality of Life Issues in Patients with HIV and Liver Disease.
Keywords: Gastroenterology .; Hepatology; Internal medicine; Gastroenterology; Hepatology; Internal Medicine